Impact of Corona Virus Disease in Health Care Professionals in Managing Patients with Positive Disease in Pakistan - Ameet Jesrani , Pari Gul , Nida Amin Khan , Seema Nayab , Riaz Hussain Awan , Palwasha Gul (Journal of Rawalpindi Medical College, 2021)
Objective The present was conducted to evaluate psychological impact of COVID-19 infection in health care professionals while treating Corona Virus positive patients. Study and Design Descriptive Observational cross Sectional study Methods and Materials The Depression, Anxiety and Stress Scale - 21 Items (DASS-21) are a set of three self-report scales designed to measure the emotional states of depression, anxiety and stress. The DASS-21 incorporated in a questionnaire form was distributed among the healthcare professionals that were involved in direct management of COVID-19 patients. 224 consented HCPs participated in this cross sectional study, during MAY 2020, nearing the end of the first wave of this pandemic in Pakistan. Results The results were broken down to scores assigned to: Anxiety (overall mean score 19.01 ± 9.2), with 192 (85.7%) HCPs experiencing moderate to extremely severe anxiety; Depression (overall mean score 18.12 ± 10), with 162 (72.3%) HCPs being moderate to extremely severely depressed; Stress (overall mean score 20.12 ± 12.0), 202 (90.1%) HCPs reporting moderate to extreme stress levels. Conclusions Our study highlights the negative effect of this pandemic, despite the steadfastness to serve, on the psychological well being of our healthcare professionals. As the corona virus pandemic continues, the levels of, anxiety, stress and depression are expected to increase among our major workforce and the main defense against the deadly virus. Hence the mental well being of our doctors and paramedics should be scrutinized often and necessary measures should be taken at a national level to ensure the better functioning of our health care system.